Increased QT Dispersion Is Linked to Worse Outcomes in Patients Hospitalized for Out‐of‐Hospital Cardiac Arrest. Issue 16 (18th August 2020) - Kosmopoulos, Marinos; Roukoz, Henri; Sebastian, Pierre; Kalra, Rajat; Goslar, Tomaz; Bartos, Jason A.; Yannopoulos, Demetris; Benditt, David G.
Abstract : Background: The incidence and mortality of out‐of‐hospital cardiac arrest (OHCA) remains high, but predicting outcomes is challenging. Being able to better assess prognosis of hospitalized patients after return of spontaneous circulation would enable improved management of survival expectations. In this study, we assessed the predictive value of ECG indexes in hospitalized patients with OHCA. Methods and Results: PR interval and QT interval corrected by the Bazett formula (QTc) for all leads were calculated from standard 12‐lead ECGs 24 hours after return of spontaneous circulation in 93 patients who were hospitalized following OHCA. PR interval and QT and QTc duration did not differentiate OHCA survivors and nonsurvivors. However, QT and QTc dispersion was significantly increased in patients who died during hospitalization compared with survivors discharged from the hospital ( P <0.01). Logistic regression indicated a strong association between increased QT dispersion and in‐hospital mortality ( P <0.0001; area under the curve, 0.8918 for QT dispersion and 0.8673 for QTc dispersion). Multinomial logistic regression indicated that the increase of QTc dispersion correlated with worse Cerebral Performance Category scores at discharge ( P <0.001; likelihood ratio, 51.42). There was also significant correlation between dispersion measures and serum potassium at the time of measurement and between dispersion measures and cumulative epinephrine administration. No difference existed regarding the number of measurable leads. Conclusions: Lesser QT and QTc dispersion at 24 hours after return of spontaneous circulation was significantly associated with survival and neurologic status at discharge. Routine evaluation of QT and QTc dispersion during hospitalization following return of spontaneous circulation might improve outcome prognostication for patients hospitalized for OHCA.